Analysis of the Business Model Canvas (BMC) on the Development of Processed Citrus Products - Andi Ridwan Makkulawu; Ilham Ahmad; Imran Muhctar (International Journal of Economics, Business and Innovation Research, 2023)
Oranges are a type of fruit with a fresh taste and vitamin C content, so it is great to consume in fresh form. Some processed citrus fruit products on the market and in minimarkets are still not in demand by consumers, this is because some products marketed are not through market research. Another problem is that the business strategies implemented by some processed orange-based products do not keep up with the times. Therefore, it is necessary to do a Business Model Canvas (BMC) to analyze business strategy. The purpose of this study is to obtain a model for developing processed citrus fruit products with market research methods and produce a business strategy for processed citrus fruit product with Business Model Canvas. The methods used are Business Model Canvas (BMC) and SWOT analysis. The results of this study show that most marketable and and preferred orange-based product of consumers are health drink products with C1000 mg vitamins and business position on the cartesius diagram iin quadrant I with IFAS (2.12) and EFAS (3.50) values, so the focus of the strategy used is the SO strategy developed in the map of 9 blocks of retionale. Keywords: bmc, processed citrus products, market research, swot. Keywords: BMC, IFAS, EAS, Citrus product, Market research, SWOT